Demographic and hematological factors associated with discordant immunologic response to antiretroviral therapy in an African cohort - Muzah, Batanayi Prinsloo (My University, 2012)
Background The therapeutic goal of HAART is sustained immune recovery and viral suppression. However some patients still have poor CD4 count responses despite achieving viral suppression. Such discordance immune response has been associated with poor clinical outcomes. We describe the prevalence of discordant immune response during the first 6-months of HAART and determine risk factors associated with this discordance at two large public sector clinics in South Africa. Methods We analysed data from 6 460 HIV-infected adults initiated onto first-line HAART at Goba and Phola Park clinics, in Johannesburg, South Africa between November 2008 and December 2009. Multivariable logistic regression models were used to estimate adjusted odds ratios (AOR) for associations between discordant immune response and clinical and demographic factors. Models were adjusted for WHO clinical stage, baseline CD4 count, education level and HAART regimen. Results At initiation of HAART, most patients were female 592(64.6%) and 803(87.6%) were initiated on 3TC-d4T-EFV/NVP. The mean CD4 count was 155 cells/mm3 (±118.4 sd), mean age was 38.5 years (±8.7 sd) and most patients had haemoglobin >11g/dL (n=645, 71.2%). By 6-months after initiation of HAART, 24% (n=220) of patients had a discordant immune response, 7% (n=67) discordant virologic 5 response and 21% (n=1359) had been lost to follow-up. In multivariable analysis, higher baseline CD4 cell count (CD4≥200cells/mm3): AOR=3.02; 95%CI 2.08-4.38; p<0.001) and moderate anemia (8-9.4 g/dL) at baseline (AOR=2.30; 95%CI 1.25-4.59; p=0.007) were the strongest predictive factors for development of discordant immune response. Conclusions We found a significant proportion of patients with discordant immune response 6-months after initiating HAART. Simple algorithms utilizing baseline characteristics can be developed for use in clinics in order to identify those patients at risk of development of discordant immune responses. Intensive monitoring of individuals at risk may improve clinical outcomes.
M.Sc.(Med.), Epidemiology and Biostatistics, Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: Antiretroviral Therapy, Highly Active